Quality by design approach assisted development and optimization of Chitosan–Vildagliptin nanoparticles using a simple desolvation technique - Anand Shripal Ammanage, Vinayak Shivamurthi Mastiholimath (Journal of Applied Pharmaceutical Science, 2025)
Type 2 diabetes mellitus is a major metabolic condition that poses a serious risk and a significant public health concern worldwide. Vildagliptin is a new class of antidiabetic drugs used to treat type 2 diabetes mellitus. In the current work, Chitosan-Vildagliptin nanoparticles (CS-VLD NPs) were developed by simple desolvation technique. A 32 factorial design and response surface methodology were used for optimization. The prepared nanoparticles underwent characterization to determine their particle size (PS), polydispersity index (PDI), entrapment efficiency (EE), FTIR, transmission electron microscopy (TEM), in vitro drug release, and release kinetics. A 3-month accelerated stability study was performed for the optimized formulation (N6). The PDI value of CS-VLD NPs was varied from 0.24 ± 0.025 to 0.39 ± 0.037, while the PSs were ranged from 118.24 ± 2.26 nm to 232.84 ± 6.79 nm. The EE values were varied from 26.54 ± 3.61 to 51.57% ± 1.52%. FTIR study had shown the compatibility of drug and polymer. TEM images were shown spherical-shaped nanoparticles. During the in vitro drug release study, sustained drug release was found up to 24 hours, followed by Higuchi kinetics. During the stability study, the optimized (N6) formulation proved its stability. The study concludes that the developed CS-VLD NPs may be a more effective approach than conventional drug delivery for the sustained release of Vildagliptin in the treatment of diabetes mellitus.
Keywords: Chitosan, vildagliptin, quality by design, diabetes mellitus, desolvation method